Development and Preliminary Italian Validation of the Emergency Response and Psychological Adjustment Scale - Diotaiuti, Pierluigi; Valente, Giuseppe; Mancone, Stefania (Frontiers in Psychology, 2021)
Evaluating the personal adaptation response to the emergency situations is very important for the prevention of mental distress, for the activation of network and community synergies and for the planning and implementation of appropriate psycho-social interventions. So far there are no short tools for the overall assessment of cognitive, emotional and behavioral responses of psychological adaptation to the emergency in the psychometric panorama. This validation study of the Emergency Response and Psychological Adjustment Scale has shown that this version is a reliable measurement for assessing people’s modes of personal response (cognitive, emotional, behavioural) in emergency contexts. The ERPAS was administered to a sample of 1,088 participants, while the concurrent validity was tested through a second administration to 600 participants along with the GSE (Generalised Self-Efficacy Scale) and the BDI-II (Beck Depression Inventory – II). Confirmatory factor analysis bore out a five-factor solution (including 17 items) with good indices of adaptation to data, e.g., χ2/df = 1.300, RMSEA = 0.024, RMSEA 90% CI = .009-.034, GFI = 0.972, AGFI = 0.959, CFI = 0.989 and NFI = 0.722. The convergent validity assessment confirmed predictive indications with variables such as cognitive and somatic depression, and perceived general self-efficacy. The analyses also showed a strong invariance across gender. The ERPAS tool prefigures application during the assessment in multiple emergency contexts (e.g. earthquakes, floods, pandemics, terrorist attacks, war events, major accidents, major fires).